The Roles of Communication and Organizational Culture in Maintaining Employeesâ Loyalty (A Case Study of Charoen Pokphand Company) - Azizah, Siti (Jurnal Ilmu Komunikasi, 2011)
Abstract: This paper attempts to investigate how communications organization is conducted by Charoen Pokphand Company (a multinational poultry company) to stop the shifting of competitorsâ employees amid the high tendency of the employeesâ shifting to competitorsâ company. This study uses explanatory case study as research method with single case design. The analysis is carried out from the perspectives of organizational culture and internal communications functions of the organization in maintaining the employeesâ loyalty. An analysis of the employeesâ shifting case id based on several notions that organizational culture is very influential on the process of communication within the organization (Ruppel and Harington 2000), how cultural management affects on the communication (Bordow and More in McKenna 2006), and the effects of cultural subsystems on the employeesâ loyalty (Eskildsen and Nussler 2000). Literature studies and interviews are performed to obtain data on several cases of employeesâ shifting which have happened at Charoen Pokphand Company. The informant is an employee who has worked at Charoen Pokphand Company for eleven years and is often received offers to move to other competitorsâ company. Offers which give better position and salary turn out to be unappealing when compared to the organizational culture and communication processes which provide work comfort.Â Abstrak: Makalah ini bertujuan untuk mengetahui lebih jauh tentang bagaimana komunikasi organisasi yang dilakukan PT. Charoen Pokphand Indonesia (sebuah perusahaan pakan ternak multinasional) dalam upayanya mencegah migrasi karyawan kompetitor ditengah tingginya mobilitas migrasi karyawan ke perusahaan kompetitor. Metode studi kasus eksplanatori digunakan sebagai metode penelitian dan menggunakan desain studi kasus tunggal. Tulisan ini dibahas dari perspektif budaya organisasi dan fungsi komunikasi internal organisasi dalam memelihara loyalitas karyawan. Pembahasan terhadap kasus migrasi karyawan ini dilakukan dengan mendasarkan pada beberapa pendapat bahwa budaya organisasi sangat berpengaruh terhadap proses komunikasi dalam organisasi (Ruppel and Harrington 2000), bagaimana manajemen budaya berpengaruh pada komunikasi (Bordow and More in McKenna 2006) dan efek subsistem budaya terhadap loyalitas karyawan (Eskildsen and Nussler 2000). Studi literature dan dan wawancara digunakan untuk memperoleh data tentang beberapa kasus migrasi karyawan yang pernah terjadi di PT. Charoen Pokphand Indonesia. Informan adalah seorang karyawan PT. Charoen Pokphand Indonesia yang sudah bekerja selama 11 tahun dan sering mendapatkan tawaran untuk berpindah dari perusahaan PT. Charoen Pokphand Indonesia ke perusahaan kompetitor. Penawaran yang lebih memberikan posisi serta gaji yang lebih baik ternyata bukan tawaran yang menarik bila dibandingkan budaya organisasi dan proses komunikasi yang memberikan kenyamanan kerja.